Variabilidades fenotípica e genotípica de estirpes de Staphylococcus aureus isoladas em casos de mastite subclínica bovina - Ferreira, Luciano Menezes [UNESP]; Nader Filho, Antonio [UNESP]; Oliveira, Erika de [UNESP]; Zafalon, Luiz Francisco; Souza, Viviane de [UNESP] (Universidade Federal de Santa Maria (UFSM), 2006)
Foram submetidas a PCR-Ribotipagem e aos testes de sensibilidade in vitro frente a 12 antimicrobianos 77 estirpes de Staphylococcus aureus isoladas em amostras de leite procedentes de 40 vacas da raça holandesa que apresentaram mastite subclínica, em uma propriedade rural localizada no Estado de São Paulo, Brasil. Os resultados obtidos revelaram quatro diferentes padrões de resistência a antimicrobianos, sendo observada a predominância de resistência à lincomicina entre 19 (24,7%) estirpes de S.aureus. As 58 (75,3%) estirpes restantes foram sensíveis aos 12 antimicrobianos testados. A PCR-ribotipagem revelou a ocorrência de nove padrões genotípicos distintos, além de apresentar uma capacidade discriminatória maior (D = 0,82) que a obtida nos antibiogramas (D = 0,42). Entre as 19 estirpes resistentes aos antimicrobianos, 14 (73,7%) foram agrupadas em três padrões de ribotipagem e, destas, 13 (92,9%) apresentaram resistência à eritromicina e à lincomicina, isoladamente ou em associação. O grande número de ribotipos e de padrões de resistência a antimicrobianos observados nesta propriedade demonstrou que há grande heterogeneidade genética em populações naturais de S. aureus, fato este que deve ser levado em consideração em programas de controle da mastite bovina.

Seventy-seven S. aureus strains, isolated in milk samples obtained from 40 Holstein cows suffering from subclinical mastitis in a dairy herd in the state of São Paulo - Brazil, were undergone to PCR-ribotyping and in vitro susceptibility testing to 12 antimicrobial drugs. PCR-ribotyping revealed nine different patterns and presented a higher discriminatory power (D = 0.82) in comparison with the in vitro antibiotic susceptibility test (D = 0.42). Moreover,, the results showed four antibiotic resistance patterns, with the resistance to lincomycin being the most predominant and comprising 19 (24.7%) S. aureus strains. The other 58 (75.3%) isolates were sensitive to all antibiotics tested. of the 19 isolates which presented resistance to antibiotics, 14 (73.7%) were grouped in three ribotypes, and 13 (92.9%) of them were resistant to eritromycin and/or lincomycin. The large number of ribotypes and antibiotic resistance patterns found in this single dairy herd showed that one must be careful when considering the results of in vitro susceptibility tests obtained from a few S. aureus strains, because there is a high heterogeneity among naturally occurring populations of S. aureus, which must be taken into consideration in control programs against bovine mastitis.
Phenotypic and genotypic variabilities of Staphylococcus aureus strains isolated from bovine subclinical mastitis
Keywords: Mastitis; Staphylococcus aureus; phenotypic and genotypic variabilities; Mastite; Staphylococcus aureus; variabilidade fenotípica e genotípica